Masticatory Adaptation to Occlusal Changes - Bourdiol, Pierre; Hennequin, Martine; Peyron, Marie-Agnes; Woda, Alain (Frontiers in Physiology, 2020)
Before dealing with the role of occlusion in human mastication, this article presents mastication in healthy oral conditions considering two points of view: four-step food transport through the bucco-pharyngeal cavity, and food control at three checkpoints. Several methods to evaluate mastication are presented: number of posterior functional units, self-administered questionnaires, granulometry of the food bolus, physiologic methods, routine clinical evaluations. Evaluation of mastication evidences the wide and frequent variability of masticatory outcome and allows defining the concepts of capacity, incapacity and successful compensative adaptation. Evolving dental wear is an example of a change in occlusion with masticatory consequences even when dental wear occurs as a normal phenomenon. Several features of dental wear are reviewed such as the concomitant tooth displacements, the dental wear origin, its possible abnormalities and their repercussion on masticatory capacity / efficiency. Then, the question to be asked is to what extent malocclusion impacts chewing. The trivial claim that malocclusion has little impact on chewing is based on casual clinical situations. This statement does not take into account the broad variety of situations covered by the ill-defined term malocclusion. There is nothing in common between morphological malocclusions such as a limited anterior dental crowding and major malocclusions resulting, for example, from maxillofacial oncological surgery, aging related tooth loss, advanced carious disease, sudden severe cerebral palsy or chronic neuromuscular deficiencies. All shades are possible between these conditions. The description of how masticatory function adapts must also encompass the occlusal rehabilitation and the chosen therapeutic method. Finally, the impact of mastication on nutrition is examined.